Fatores preditivos e funcionalidade em zumbido - Lima, Daviany Oliveira (2021)
Introduction: The heterogeneity of tinnitus results in the scarcity of well-designed studies, including those on its risk factors. Most tinnitus management strategies focus on improving quality of life, and it is important to identify the main factors associated with the symptom and understand the impact on functionality, in order to guide clinical management and assist in therapy. Objective: to investigate the main risk factors associated with tinnitus and the impact on functionality through the classification of a tinnitus assessment instrument. Methodology: This dissertation is structured in two manuscripts: Article1 "Association of risk factors for tinnitus in adults", an observational, cross-sectional, retrospective analytical study through the descriptive analysis of the profile of patients cared for in a service for patients with buzz; Article 2 “Application of the international classification of functionality, disability and health in the assessment of people with tinnitus”, a retrospective study with documental analysis of secondary data from the database of a service specialized in treating tinnitus symptoms. Results: There is an association of tinnitus with hypersensitivity to sounds, ear fullness and hearing loss. The symptom to a moderate degree has significant interference with sleep, concentration and emotional issues. According to the ICF classification, such damages result in 59% preserved functionality and 40% incapacity. Of these 59%, there was a greater impact on the functional (40.42%) and catastrophic (44.14%) subscales. In the disability data, an impact considered severe was observed, with a predominance of higher results in the emotional subscale (78.9%). Final Considerations: Understanding the main factors associated with tinnitus is important to understand the impact of tinnitus, thus providing expansion and development of public policies and therapeutic possibilities for this population.